PENINGKATAN HASIL BELAJAR MENENTUKAN GRADIEN, PERSAMAAN, DAN GRAFIK GARIS LURUS MELALUI STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING SISWA KELAS VIII A SMP NEGERI 2 KECAMATAN PONOROGO - Pujianingrum, Sukesi (Educatio Vitae, 2016)
The research entitled “The Improvement of The Results of The Study in The Topic of Determining Gradient, Equations, and Straight Line Graphs through The Learning Strategy of Active Knowledge Sharing of The Eighth Grader A in The State Secondary School 2 Ponorogo in The Second Semester 2013-2014 Academic Year” is a research of class act which is conducted in 3 cycles consisting of 6 meetings. Each meeting consists of 2 X 40 minutes. Every cycle includes the activities of planning, implementation, observation, and reflection. The data are taken by using test, interviewing, distributing questionnaires and journal. The aim of this research is to know the improvement of the results of the study of the students. The role of the learning study called Active Knowledge Sharing in improving the results of the study in the topic of “Determining Gradient, Equivalence, and Straight Line Graphs” is noticed by the improvement of mean score which consists of 74.84 in cycle I; 80.94 in cycle II ; and 85,94 in cycle III. Moreover, there is also the improvement of study accomplishment that reaches 68.75% in cycle I, 87.50% in cycle II, 100% in cycle III. The research proves that the use of Active Knowledge Sharing learning strategy in the process of learning could improve the result of study in Mathematics in the topic of “Determining Gradient, Equivalence, and Straight Line Graphs.” Key Words: Competence,  Results of Sstudy, Active Knowledge Sharing, Mathemathics